2016
DOI: 10.1248/bpb.b15-00630
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Bisphosphonates and Mineral Water: Study of Oral Risedronate Absorption in Rats

Abstract: Bisphosphonates are antiosteoporotic agents prescribed for patients with osteoporosis. Drug package inserts for bisphosphonate supplements indicate that their bioavailability is reduced by high levels of metal cations (Ca 2 , Mg 2 , etc.). However, standards for these cations in water used for taking risedronate have not been defined. Here, we examined the effect of calcium and magnesium in mineral waters on the bioavailability of the third-generation bisphosphonate, risedronate, following oral administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The test formulation was composed of a novel, dispersible, FDC preparation that contained 4 tablets of abacavir 150 mg/dolutegravir 10 mg/lamivudine 75 mg mixed with 3.0 mg/mL of acesulfame potassium, 1.2 mg/mL of sucralose, and 1.2 mg/mL of strawberry-cream flavor in 40 mL of either high-mineral content water (calcium, 468 mg/L; magnesium, 74.5 mg/L; Contrex, Nestlé Waters, Vevey, Switzerland) or purified, zero-mineral content water. 15 Participants were randomized (1:1:1:1:1) to 1 of 5 treatment groups over 5 dosing periods as follows (Figure, Supplemental Digital Content 1, http://links.lww.com/QAI/B218 , which illustrates the study design): reference treatment of abacavir 600 mg/lamivudine 300 mg plus 4 tablets of dolutegravir 10 mg administered with 200–250 mL of purified, zero-mineral content water without dispersion (tablets were nondispersible, film-coated); abacavir/dolutegravir/lamivudine dispersed in high-mineral content water and administered immediately; abacavir/dolutegravir/lamivudine dispersed in high-mineral content water with administration delayed for 30 minutes; abacavir/dolutegravir/lamivudine dispersed in purified, zero-mineral content water and administered immediately; and abacavir/dolutegravir/lamivudine dispersed in purified, zero-mineral content water with administration delayed for 30 minutes. All treatments were orally administered in the morning on an empty stomach, and food intake was prohibited for 4 hours following administration.…”
Section: Methodsmentioning
confidence: 99%
“…The test formulation was composed of a novel, dispersible, FDC preparation that contained 4 tablets of abacavir 150 mg/dolutegravir 10 mg/lamivudine 75 mg mixed with 3.0 mg/mL of acesulfame potassium, 1.2 mg/mL of sucralose, and 1.2 mg/mL of strawberry-cream flavor in 40 mL of either high-mineral content water (calcium, 468 mg/L; magnesium, 74.5 mg/L; Contrex, Nestlé Waters, Vevey, Switzerland) or purified, zero-mineral content water. 15 Participants were randomized (1:1:1:1:1) to 1 of 5 treatment groups over 5 dosing periods as follows (Figure, Supplemental Digital Content 1, http://links.lww.com/QAI/B218 , which illustrates the study design): reference treatment of abacavir 600 mg/lamivudine 300 mg plus 4 tablets of dolutegravir 10 mg administered with 200–250 mL of purified, zero-mineral content water without dispersion (tablets were nondispersible, film-coated); abacavir/dolutegravir/lamivudine dispersed in high-mineral content water and administered immediately; abacavir/dolutegravir/lamivudine dispersed in high-mineral content water with administration delayed for 30 minutes; abacavir/dolutegravir/lamivudine dispersed in purified, zero-mineral content water and administered immediately; and abacavir/dolutegravir/lamivudine dispersed in purified, zero-mineral content water with administration delayed for 30 minutes. All treatments were orally administered in the morning on an empty stomach, and food intake was prohibited for 4 hours following administration.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, besides inflammation, a strong physiological/cellular link between a rising intracellular ratio of calcium to magnesium and aspects of metabolic syndrome, including hypertension, hyperinsulinemia, insulin resistance and left ventricular cardiac hypertrophy, has been described [170]. Considering that postmenopausal women were included in some of the studies discussed in this review (as for example in [73]) and menopause is a risk factor for osteoporosis [171], the consumption of mineral waters with calcium may impair bisphosphonates bioavailability [37,172].…”
Section: Discussionmentioning
confidence: 99%
“…The results of preclinical studies indicated that alendronate and risedronate absorption may decrease with the increasing concentration of calcium in mineral water used for drug administering [30,31]. As instructed by prescribing guidelines, oral bisphosphonates are recommended to be taken with tap water, to minimize the risk of malabsorption caused by calcium and other cations present in mineral and spring waters.…”
Section: Problem With Water Typementioning
confidence: 99%